A charge-adaptive nanosystem for prolonged and enhanced in vivo antibiotic delivery. Issue 37 (14th April 2016) - Chu, Liping; Gao, Honglin; Cheng, Tangjian; Zhang, Yumin; Liu, Jinjian; Huang, Fan; Yang, Cuihong; Shi, Linqi; Liu, Jianfeng
Abstract : A poly(β-amino ester)-based nanocarrier with the acid-dependent charge conversion characteristic prolonged and enhanced the in vivo vancomycin delivery. Abstract : Herein we report on a charge-adaptive nanosystem for prolonged and enhanced in vivo antibiotic delivery. The nanocarrier achieves acid-dependent charge conversion, thus prolonging the circulation time and enhancing antibiotic accumulation in subcutaneous inflammation models.